Anaesthesia for Live Related Liver Transplantation: Experience at a Teaching Hospital in Abroad - Sadar, K; Hannan, MA; Aneja, S (Bangladesh Medical Journal, 2012)
ordinary, challenging and very much special for anaesthesiologists. The liver transplantation programme at Indraprastha Apollo Hospital, Delhi, India has been running since 1998. Both live related and cadveric liver transplantations are performed and it is about 100 to 120 per year. In this prospective study, the anaesthetic aspects of 10 live related liver transplantations are reviewed. Here we focused on anaesthetic technique used; indications for liver transplantation and type of graft transplanted; survival rate; duration of anaesthesia and cost; intra-operativeLive related liver transplantation is no longer experimental. It is the therapeutic option for patients with chronic liver failure. Adequate logistic and prompt laboratory service, availability of blood products, maximum invasive and non invasive monitoring is mandatory for better outcome. BMJ 2010; 39(3)